The Effect of Neurofeedback Training on Dynamic Balance of Young Men - Hasan Mohammadzadeh; Mohammad Ali Nazari; Mandana Heidari (رشد و یادگیری حرکتی ورزشی, 2015)
Physical balance is one of the important factors in daily sport activities.Dynamic balance helps maintain the balance of those forces imposed on body insports and an increase in this balance improves motor and sport performance. Theaim of this study was to determine the effects of neurofeedback training on dynamicbalance of young men. 24 male undergraduate students voluntarily participated inthis study and were involved in a double-blind design including control andexperimental groups. The experimental group participated in neurofeedbacktraining including the inhibition of brainwaves of 4-7 Hz and the reinforcement ofbrainwaves of 15-18 Hz at O1-O2 regions of the hindbrain for 10 sessions and 30minutes per session. Participants in the control group were exposed to the samecondition, but instead they were provided with sham feedback. EEG and dynamicbalance tests were administered before, at the end of the fifth and tenth sessions oftraining for both groups. The results indicated that dynamic balance significantlyimproved in the fifth session and posttest. The findings demonstrate thatneurofeedback training can enhance dynamic balance of young men. It issuggested that this training should be used to increase dynamic balance of athletes.